PENGEMBANGAN E-LKPD MATERI TEKS BERITA BERBASIS PENDEKATAN PEMBELAJARAN MENDALAM BAGI SISWA KELAS XI SMA - Chairani Dwi Putri; Achmad Yuhdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop an electronic student worksheet (e-LKPD) based on an in-depth learning approach that is in accordance with the needs of high school grade XI students in understanding news text material. Preliminary findings show that learning is still dominated by printed books and printed LKPD which is suspected to cause monotonous learning so that students are passive and have difficulty understanding news text material. This research uses the Research and Development (R&D) method with a 4D development model that is simplified to 3D without proceeding to the dissemination stage. The e-LKPD developed has been validated by material expert validators and media expert validators which were then conducted on a limited scale trial with 10 students in grades XI-7. The validation results showed that e-LKPD was at the